2017
DOI: 10.1159/000470902
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Alters the Postnatal Development of the Rat Cerebellum

Abstract: Intrauterine growth restriction (IUGR) is a major cause of antenatal brain injury. We aimed to characterize cerebellar deficits following IUGR and to investigate the potential underlying cellular and molecular mechanisms. At embryonic day 18, pregnant rats underwent either sham surgery (controls; n = 23) or bilateral uterine vessel ligation to restrict blood flow to fetuses (IUGR; n = 20). Offspring were collected at postnatal day 2 (P2), P7, and P35. Body weights were reduced at P2, P7, and P35 in IUGR offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
4
18
0
Order By: Relevance
“…The linear density of fibres (fibres/mm) was then determined by dividing the number of fibres by length of the line. We also qualitatively assessed the morphology of Bergmann glia, for example for evidence of fibre disorganisation (tangled or irregularly orientated fibres), and disrupted fibre integrity (damaged/degenerating fibres and disconnected fibres, i.e., those that did not extend the full length from the IGL to the upper EGL) as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear density of fibres (fibres/mm) was then determined by dividing the number of fibres by length of the line. We also qualitatively assessed the morphology of Bergmann glia, for example for evidence of fibre disorganisation (tangled or irregularly orientated fibres), and disrupted fibre integrity (damaged/degenerating fibres and disconnected fibres, i.e., those that did not extend the full length from the IGL to the upper EGL) as previously described [24]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, children who were GR in utero have decreased white matter volume in the cerebellum [17] and cerebellar underdevelopment in IUGR infants is linked to altered cerebellar connectivity and function [18]. In animal models of IUGR induced via either chronic [19-23] or acute [24] placental insufficiency, we have already demonstrated that several aspects of cerebellar development are adversely affected when assessed pre- and postnatally. In GR guinea pigs induced by chronic placental insufficiency (CPI) throughout the second half of gestation [21], there are significant reductions in: the number of Purkinje cells [25], the volumes of the molecular layer (ML), internal granular layer (IGL) and white matter [19, 22, 25], and alterations in the maturation of myelin [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above-mentioned organs, Trop2 is also expressed in lungs [ 17 , 18 ], intestines [ 19 ], stomach [ 20 ], bladder [ 21 ], and kidneys [ 22 ] during embryonal and fetal development. Trop2 protein was also detected in granule cells in all layers of the developing cerebellum, particularly in postmitotic cells, suggesting its function in regulation of cell migration [ 23 ]. In the damaged adult stomach, Trop2 is re-expressed and might be associated with regeneration processes [ 20 ].…”
Section: Trop2 In Healthy Tissue and Developmentmentioning
confidence: 99%
“…; McDougall et al . ). In the rat, IUGR leads to delayed neuronal migration in the cerebral cortex (Sasaki et al .…”
Section: Introductionmentioning
confidence: 97%